(untitled) (International Journal of Food and Nutritional Sciences, 2022)
When compacted and dried, soil cement can be a mixture of soil, hydraulic cement, and water that creates a solid and durable pavement basis. Concerns about suitable internal control procedures and the testing process for soil cement have been raised as a result of construction practices and variations in core strength data. To answer these questions, numerous types of soil cement buildings were examined, and conclusions were drawn from them that include grouting with soil cement in various structures. The specifics of the properties of soils and cement are briefly addressed. Additionally, a thorough explanation of the applications and hence the future scope of our study is provided.